Islamic Educational Provisions in South Korea and Indonesia: A Comparison - Zamakda Allison, Safwaan (Journal of Islamic Education Students (JIES), 2023)
This essay seeks to uncover, examine and analyse the provision of Islamic education in both Indonesia and South Korea. Comparisons were made in respect of infrastructure, curriculum, scope and reach, professionalism, funding and other areas, and potential for improvements identified. By examining existing research, publications, newspaper articles, journal publications, statistics and other data and information sources, it is apparent that Korea is severely lacking in Islamic education provisions, whereas this is not generally the case in Indonesia. This is primarily owing to demographic, historical and social reasons. However, with the declining population of Korea, and a birth-rate unable to reach even a stable replacement-rate, Korea will be forced to meet labour needs by way of immigration. Accordingly, with the arrival of more Muslim workers, and a higher number of Muslim students, the Muslim of population is likely to significantly increase, as will the rate of Korean Muslims by way of conversion to Islam.